Study of Nd substitution in Bi–(Pb)–Sr–Ca–Cu–O high-Tc superconductors - Celebi, S.; Malik, A.I.; Halim, S.A. (Elsevier, 2002)
Measurements of complex AC susceptibility χ = χ′ + χ″ as a function of temperature and AC field amplitude have been carried out on rectangular bar-shaped high-temperature superconductors with nominal composition of Bi1.6Pb0.4Sr2(Ca1-xNdx) 2Cu3Oδ superconducting samples prepared by the solid-state reaction method. The effect of Nd-substitution on the Bi-(Pb)-Sr-Ca-Cu-O system has been investigated in terms of an AC susceptibility study. It was found that as the amount of Nd content x increases, the transition temperature decreases. Temperature-dependent critical current density was deduced from AC susceptibility data. In spite of a slight decrease of Tc, the highest pinning strength parameters (Jcm (T = 0) and temperature exponent n) were obtained for the sample with x = 0.02.